1999
DOI: 10.1111/j.1559-1816.1999.tb01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Odor and Coping Style on Negative Affect, Anger, Arousal, and Escape1

Abstract: Trait coping, state anger, perceived arousal, blood pressure, negative affect, and escape behavior were measured in a sample of 240 undergraduate males and females exposed to 1 of 4 foul-odor conditions or to a no-odor condition. Consistent with Baron and Bell's (1976) negative-affect-escape model, it was hypothesized that people exposed to noxious odors would experience increased negative affect and heightened motivation to escape the situation. Results showed that negative affect and motivation to escape, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The most dramatically affected mood dimensions were happiness and depression, which were impaired relative to baseline for the entirety of the study protocol. While this study is one of the first to demonstrate a potential relationship between the laboratory environment and negative mood, this finding is in line with previous research that has indicated negative mood in response to environmental factors such as temperature, odor and confinement . While the laboratory was highly controlled in regards to temperature and cleanliness, confinement or other aspects of the laboratory environment, such as restricted access to sunlight and exercise, may have negatively influenced mood.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The most dramatically affected mood dimensions were happiness and depression, which were impaired relative to baseline for the entirety of the study protocol. While this study is one of the first to demonstrate a potential relationship between the laboratory environment and negative mood, this finding is in line with previous research that has indicated negative mood in response to environmental factors such as temperature, odor and confinement . While the laboratory was highly controlled in regards to temperature and cleanliness, confinement or other aspects of the laboratory environment, such as restricted access to sunlight and exercise, may have negatively influenced mood.…”
Section: Discussionsupporting
confidence: 89%
“…While this study is one of the first to demonstrate a potential relationship between the laboratory environment and negative mood, this finding is in line with previous research that has indicated negative mood in response to environmental factors such as tem-perature, odor and confinement. [6][7][8][26][27][28] While the laboratory was highly controlled in regards to temperature and cleanliness, confinement or other aspects of the laboratory environment, such as restricted access to sunlight and exercise, may have negatively influenced mood. Indeed, Wilhelm and Grossman 4 suggest that the laboratory as an unfamiliar and potentially threatening environment may influence emotional responses in experimental research.…”
Section: Discussionmentioning
confidence: 99%
“…of waiting in a room while exposed to lavender or a no-scent control condition, but self-report differences in mood were associated with exposure to the lavender scent. Other researchers have not reported physiological changes based on scent exposure (Asmus & Bell, 1999;Romine, et al, 1999) and those who do report them to be relatively short lived (Yagyu, 1994;Diego, et al, 1998). Regarding mood, when pleasantness ratings were considered, rosemary exposure was associated with high scores on the tension-anxiety subscale of the POMS inventory.…”
Section: Discussionmentioning
confidence: 92%
“…Based on prior research, it was predicted that exposure to a scent would be associated with physiological changes in heart rate and temperature, as well as self-reported mood changes as assessed by the Profile. Since there is evidence to support the idea that aromas affect mood and reduce anxiety given differences in their hedonic qualities (Baron & Thomley, 1994;Martin, 1996;Raudenbush, et al, 2001) and prior research suggests the importance of individual percep- tions of scent pleasantness (Koga, 1989;Yagyu, 1994;Asmus & Bell, 1999), it was predicted that changes in physiology and mood would be mediated by participants' ratings of scents' pleasantness. Since preliminary statistical analyses showed significant differences in perception of scent for the three groups, pleasantness served as a covariate in all statistical analyses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation